If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 4) = 3(2x + -1) Reorder the terms: 5(4 + x) = 3(2x + -1) (4 * 5 + x * 5) = 3(2x + -1) (20 + 5x) = 3(2x + -1) Reorder the terms: 20 + 5x = 3(-1 + 2x) 20 + 5x = (-1 * 3 + 2x * 3) 20 + 5x = (-3 + 6x) Solving 20 + 5x = -3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 20 + 5x + -6x = -3 + 6x + -6x Combine like terms: 5x + -6x = -1x 20 + -1x = -3 + 6x + -6x Combine like terms: 6x + -6x = 0 20 + -1x = -3 + 0 20 + -1x = -3 Add '-20' to each side of the equation. 20 + -20 + -1x = -3 + -20 Combine like terms: 20 + -20 = 0 0 + -1x = -3 + -20 -1x = -3 + -20 Combine like terms: -3 + -20 = -23 -1x = -23 Divide each side by '-1'. x = 23 Simplifying x = 23
| .7(.1x+.1)=-.7 | | 14(v+2)-2v=4(3v+3)-18 | | x+31=-48 | | (3x-1)(2x^2+3x-3)=0 | | 9.5-23.5p=3.5(9p+3) | | (5v-6)(5+v)=0 | | 10x+6y+6+17x-16y-16= | | 4(y+3)-3=25 | | 11(z+1)-3(z-1)=3(z-2)+4(z-3) | | 9x-2(-5+7)=-8x-5 | | 4(9-14)=n-3 | | 67-5*7= | | (x+1)3=216 | | -0.04x^2+0.64x+1.94=0 | | (3x-2)(2x+6)=0 | | 9x-(8x+9)=9x-33 | | 30y+8=32 | | (2-x)(2+x)=0 | | 5=9x-8x+6 | | (7-x)(x^2+2x-3)=0 | | 6(6-4)=12y | | x+27=-52 | | x^2=128-8x | | 11x^2+2x=10 | | (7a^2-2a+6)-(-5a^2+3)=0 | | 3x+8(x-1)=0 | | -9.9-26.7=6.1-24.7r | | D^2+3d+4=0 | | 4x^2+7x+3=6 | | -9.9-26.7=6.1-24.7 | | (1.2x^5-5x^3-0.7)+(3.7x^5+3)=0 | | 2m^2-13m=0 |